The role of time in the context of Nazi terror: An analysis of Stefan Zweig’s The Royal Game - Wilk, Anna (Acta Universitatis Lodziensis. Folia Germanica, 2023)
Stefan Zweig, an outstanding Austrian writer of the 20th century, referring to Johann Wolfgang Goethe’s theory of the novella, depicts in his The Royal Game an unheard story: the meeting of two talented chess players. It is a collision of two extremes, personifying barbarism and humanism. This article traces how Zweig employs time in his work on two levels: historical and psychological. A detailed analysis explores how Zweig portrays the realities of National Socialist terror and its impact on the human psyche.